PENGARUH KESADARAN HALAL, LABEL HALAL, DAN BAHAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN ULANG BODY LOTION SCARLETT WHITENING PADA MAHASISWA MUSLIM FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS JEMBER - Diah Ayu Nupuspitasari; Lusiana Ulfa Hardinawati; N. Ari Subagio (VALUE: Journal of Business Studies, 2022)
The study was conducted to test and analyze the partial and simultaneous effect of halal awareness, halal labels, and product ingredients on the decision to repurchase Scarlett Whitening body lotion among Muslim students at the Faculty of Economics and Business, University of Jember. The population is students of the Faculty of Economics and Business, University of Jember who have active undergraduate status and have purchased Scarlett Whitening body lotion . This study determines the number of samples through purposive sampling method totaling 100 samples. By using multiple linear regression analysis method. The results of the t test show that t count on the halal awareness variable is 2.157 with a significance value of 0.034, which means that halal awareness has a significant effect on repurchasing decisions. The results of the t test show that the t count on the halal label variable is 2.051 with a significance value of 0.043, which means that the halal label has a significant effect on repurchasing decisions. The results of the t test show t count on the variable product ingredients 2.392 with a significance value of 0.019, which means that product ingredients have a significant effect on repurchasing decisions. Whereas the results of the F test simultaneously have a significant influence on the decision to repurchase Scarlett Whitening body lotion for Muslim students at the Faculty of Economics and Business, University of Jember.